2009
DOI: 10.1007/s10286-009-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

The Valsalva maneuver in Chagas disease patients without cardiopathy

Abstract: ChD patients without cardiopathy have reduced VR values compared to healthy controls, indicating early vagal dysfunction. Most previous studies could not detect this impairment due to small study samples and insufficient statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Normal autonomic modulation of the heart is also encountered in chagasics with any form of the disease. When present, the disturbance occurs with variable severity according to the chronic form of the disease and even between subjects affected with the same form 8,9,17,[30][31][32][33][34][35][36][37] . Chronically infected children with the indeterminate form also show cardiac autonomic dysfunction 38 .…”
Section: Cardiac Autonomic Nervous System In Chagas Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Normal autonomic modulation of the heart is also encountered in chagasics with any form of the disease. When present, the disturbance occurs with variable severity according to the chronic form of the disease and even between subjects affected with the same form 8,9,17,[30][31][32][33][34][35][36][37] . Chronically infected children with the indeterminate form also show cardiac autonomic dysfunction 38 .…”
Section: Cardiac Autonomic Nervous System In Chagas Diseasementioning
confidence: 99%
“…The inability to achieve adequate tachycardia and blood pressure stabilisation upon standing has also been demonstrated [74][75][76] . Depressed sensitivity of the baroreflex mechanism resulting in blunted bradycardia or tachycardia in response to acute elevation or reduction of arterial pressure has been observed 32,77 , as have altered baroreflex responses traduced by deficient heart rate responses during and after the Valsalva manoeuvre in chagasics with any form of the disease 8,33,36,78,79 . Additionally, moment-to-moment heart rate variability is variably depressed in chagasic subjects both in supine and standing positions 9,10,39,41,46,68,80 .…”
Section: Disturbed Cardiovascular Homeostatic Neural Regulationmentioning
confidence: 99%
“…Patients with Chagas disease, for example, are known to have lower Valsalva ratios than healthy controls, but a recent metaanalysis found the average Valsalva ratio among Chagas patients to be 1.74, which is well within the limits of normal. 3,33 Likewise, previous studies have demonstrated differences between PLR parameters of healthy and diabetic subjects, and PLR abnormalities can be found among patients with diabetes with and without abnormalities on CAT. 14,15,[34][35][36] Abnormal PLRs have been associated with future microvascular disease and may be associated with future CAT abnormalities.…”
Section: Discussionmentioning
confidence: 89%
“…Autonomic balance assessment using the Valsalva maneuver has been widely used in chagasic patients (21) (30) (31) and showed no difference between the groups examined in the present study. Similarly, a recent meta-analysis (32) demonstrated that only one of the seven studies analyzed found a signifi cant difference in the Valsalva ratio between healthy individuals and chagasic patients without cardiopathy. The authors also reported that in certain studies that did not detect any signifi cant difference, other autonomic indexes (such as respiratory sinus arrhythmia) were able to recognize reduced heart vagal modulation in ChD patients without cardiopathy.…”
Section: Autonomic Balance In Chagas Disease Patientsmentioning
confidence: 87%